The Significance and Features of Sports Building Structures in Construction - Adilovna, Qodirova Surayya; Atkhamovna, Aripova Nasiba; Shakhnazarovich, Rakhimov Lazizbek (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the features of the structures of sports facilities, their dependence on the form-wind, functional-technology, accepted material of the sports facility.Constructive solutions used in sports buildings were evacuated and proposals were made to take them into account in the process of silencing.